Effect of egg weight on hatching characteristics of emu eggs - JAGATHEESAN, P N RICHARD; ANANDH, M ANNA; KUMAR, P SENTHIL (The Indian Journal of Animal Sciences, 2014)
The study was carried out to investigate the effects of egg weight on hatchability traits in emu (Dromiceius novaehollandiae) eggs. Emu eggs (393) that hatched from 3 different egg weight groups (below 500 g (G 1), 501 to 600 g (G 2) and above 601 g (G 3)) were used in the experiment. Hatching traits such as percentage of infertile eggs, early embryonic mortality, late embryonic mortality, dead-in-shell, chicks hatched out, total egg hatchability, fertile egg hatchability, fertility and chick livability were investigated. The meanÂ±SE percentage of early embryonic mortality, late embryonic mortality, dead-in-shell, chicks hatched out, total egg hatchability, fertile egg hatchability, fertility and chick livability were statistically significant for different egg weight groups. The better hatching traits and livability of chicks were obtained from the medium emu eggs weighed between 501 and 600 g then the heavy (above 601 g) and small (below 500 g) egg weight groups.